LARVAE OF ANISAKIDAE SKRJABIN & KAROKHIN, 1945 (NEMATODA, ASCARIDOIDEA) IN LOPHIUS GASTROPHYSUS MIRANDA-RIBEIRO, 1915 (ACTINOPTERYGII, LOPHIIDAE) FROM THE COASTAL ZONE OF THE STATE OF RIO DE JANEIRO, BRAZIL - Vieira, Fabiano M. (2012)
The morphological and quantitative data of the larvae of Anisakidae that parasitize Lophiusgastrophysus Miranda-Ribeiro, 1915 were recorded from a marine fish of commercial importance, onthe coast of the Rio de Janeiro state. Thirty six specimens of L. gastrophysus were necropsied. Thefishes were obtained in Cabo Frio, north coast of the state of Rio de Janeiro (23º S and 42º W) and themunicipality of Rio de Janeiro, from the coast of Rio de Janeiro state (21-23° S and 41-45° W). Wefound five species of anisakid larvae: Anisakis type I, Terranova sp., Contracaecum sp.,Hysterothylacium sp. and Raphidascaris sp. The larvae of Anisakis type I were found with prevalence(P) of 22.2% and mean abundace (MA) of 0.53 larvae per host necropsied. The third stage larvae ofTerranova sp. were collected with a P=8.3% and MA=0.08. Contracaecum sp. was observed atP=8.3% and MA=0.08. Hysterothylacium sp. was observed at P=25% and MA=0.47. The larvae ofRaphidascaris sp. were recorded with P=11.1% and MA=0.42. The present study is the first record ofAnisakis type I, Terranova sp. and Contracaeum sp. parasitizing L. gastrophysus of the coast of theRio de Janeiro state.